Enhanced mechanical properties of HfMoTaTiZr and HfMoNbTaTiZr refractory high-entropy alloys. (July 2015) - Juan, Chien-Chang; Tsai, Ming-Hung; Tsai, Che-Wei; Lin, Chun-Ming; Wang, Woei-Ren; Yang, Chih-Chao; Chen, Swe-Kai; Lin, Su-Jien; Yeh, Jien-Wei
Abstract: Although refractory high-entropy alloys have exceptional strength at high temperatures, they are often brittle at room temperature. One exception is the HfNbTaTiZr alloy, which has a plasticity of over 50% at room temperature. However, the strength of HfNbTaTiZr at high temperature is insufficient. In this study, the composition of HfNbTaTiZr is modified with an aim to improve its strength at high temperature, while retaining reasonable toughness at room temperature. Two new alloys with simple BCC structure, HfMoTaTiZr and HfMoNbTaTiZr, were designed and synthesized. The results show that the yield strengths of the new alloys are apparently higher than that of HfNbTaTiZr. Moreover, a fracture strain of 12% is successfully retained in the HfMoNbTaTiZr alloy at room temperature. Highlights: Both HfMoTaTiZr and HfMoNbTaTiZr alloys have simple BCC structure. The elevated temperature properties and microstructure evolution of both alloys are investigated. HfMoNbTaTiZr has better combination of strength and plasticity than HfMoTaTiZr. The yield strength of HfMoNbTaTiZr is six times that of HfNbTaTiZr at 1200 °C. HfMoTaTiZr and HfMoNbTaTiZr have great potential in high-temperature applications.